Effects of increased transparency on political divides and MP behavior: Evidence from televised question hours in the Finnish Parliament - Jeremias Nieminen; Salla Simola; Janne Tukiainen (Aboa Centre for Economics (ACE), 2023)
We study the causal effects of increasing the transparency of parliamentary speeches on polarization and other types of MP behavior. Our research design utilizes the 1989 introduction of TV broadcasting to those Finnish government's parliamentary question hours held on the first Thursday of every month. In contrast, the question hours held on other Thursdays of the month were not televised until 2007, allowing us to use difference-in-differences to estimate causal effects on political divides and MP behavior. We find a positive effect on government-opposition divides but no evidence that the TV broadcasting of question hours would affect left-right polarization, differences between individual parties, or within-party group differences. Regarding other types of MP responses, we observe an increase in attendance and a negative effect on the number of speeches but no effects on topics discussed, speech length, or interruptions. Our results suggest there is no trade-off between increased transparency and left-right polarization but that the presence of TV cameras can fuel other political divides and behavior. Our results regarding higher attendance suggest that transparency may increase politicians' effort.
Keywords: D72; L82; P00; 330; media; polarization; transparency; text analysis; difference-in-differences